Addressing human mobility in national climate policy: Insights from updated Nationally Determined Contributions (NDCs) in South America - Diogo Andreola Serraglio; Benjamin Schraven; Natalia Burgos Cuevas (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
Whereas South American countries are experiencing increased population movements in the context of climate change, the international climate governance agenda calls for the adoption of specialised legislation and for enhanced cooperation among different policy frameworks. The revision and update of the Nationally Determined Contributions (NDCs) provide a window of opportunity to mainstream human mobility discussions in climate policy frameworks and, thus, support the uptake of effective measures to address the topic. This briefing paper provides an overview of how the climate change-human mobility nexus has been addressed in the NDCs submitted thus far by South American countries and identifies pathways towards improved management of population movements in revised NDCs. To date, a partial integration of the human mobility perspective prevails: References to the topic indicate a slow - but progressive - acknowledgment of the impacts of a changing climate in vulnerable communities, which may include human displacement. Given the urgent need to move forward from the recognition of the topic to the establishment of effective measures to tackle forced population movements associated with the impacts of climate change, the updating of NDCs - currently under way in the region - entails an opportunity to incorporate strategies aimed at enhancing the management of human mobility. Ongoing discussions linked to the inclusion of the human mobility dimension should happen in a holistic manner, taking socio-environmental approaches into consideration. Human displacement and adaptation to climate change are akin processes that need to be aligned with mitigation and related measures. An improved adaptation component of NDCs depends on the participation of distinct actors (such as national departments and agencies, as well as non-governmental and civil society organisations focussed on climate adaptation) at the national level, and not only those dealing with mitigation strategies. Likewise, it should take the incorporation of practical and evidence-based measures into account. These include, for instance, methods to promote the consultation and effective participation of affected communities and strategies to strengthen their resilience. Furthermore, revised NDCs should call for governance and legal frameworks that include a clear definition of roles and the establishment of effective measures, rooted in the commitment to protect the human rights of affected and vulnerable populations. Revised NDCs should set up policy options to prepare for and respond to human displacement, aiming to reduce communities' vulnerability and exposure. The recognition of human mobility in the context of climate change as a common challenge faced by South American countries entails a window of opportunity to enhance the development of effective measures to address the topic, as well as to foster the implementation of coherent long-term strategies that go beyond short-term political priorities.
Keywords: 330